The MVA vector expressing the F protein of bovine respiratory syncytial virus is immunogenic in systemic and mucosal immunization routes = El vector viral MVA que expresa la proteína F del virus respiratorio sincicial bovino es inmunogénico al administrarse por vía sistémica y por mucosas - Ferella, Alejandra (2023)
Bovine respiratory syncytial virus (BRSV) affects both beef and dairy cattle, reaching morbidity and mortality rates of 60---80% and 20%, respectively. The aim of this study was to obtain a recombinant MVA expressing the BRSV F protein (MVA-F) as a vaccine against BRSV and to evaluate the immune response induced by MVA-F after systemic immunization in homologous and heterologous vaccination (MVA-F alone or combined with a subunit vaccine), and after intranasal immunization of mice. MVA-F administered by intraperitoneal route in a homologous scheme elicited levels of neutralizing antibodies similar to those obtained with inactivated BRSV as well as better levels of IFN- secretion. In addition, nasal administration of MVA-F elicited local and systemic immunity with a Th1 profile. This study suggests that MVA-F is agood candidate for further evaluations combining intranasal and intramuscular routes, in order to induce local and systemic immune responses, to improve the vaccine efficacy against BRSV infection.